Production of BRS Itaim cowpea cultivar based on plant population density - Pivetta, Laerte Gustavo; Olibone, Dácio; Silva, Edvan Costa da; Olibone, Ana Paula; Keres, Gilberto; Júnior, José Ângelo Nogueira de Menezes (Scientia Agraria Paranaensis, 2019)
Cowpea has great potential for cultivation and rotation in Mato Grosso State and in Brazilian Cerrado due to the large area available in these locations in the off-season. The aim of the current study is to analyze the yield of cowpea (BRS Itaim cultivar) grown in non-irrigated soil in Sorriso County-MT, based on plant population density. The experiment was carried out in commercial area, on March 8, 2015; it followed a randomized block design, with six population densities and four replicates. Population densities comprising 80, 120, 160, 200, 240, and 280 thousand plants per hectare were used in the experiment. Experimental plots encompassed four 5-meter-long rows with 0.45-meter spacing between them. Final plant stand (plants ha-1), number of pods per plant, number of grains per pod, pod length (cm), weight of one hundred grains (g) and grain yield (kg ha-1) in the useful plot were evaluated at harvest time. The number of pods per plant has linearly decreased as population density increased. The number of seeds per pod, pod length and weight of one hundred grains did not change due to population density. Population density of 230 thousand plants ha-1 has enabled the highest grain yield under the tested conditions.